Challenges and Prospects of E-Learning for Prison Education in Nigeria - Adeyeye, Biliamin Adekunle (European Scientific Journal, ESJ, 2019)
Prison education is principally aimed at improving the inmate’s skills and employability by means of formal, technical and vocational education to reduce recidivism. Sceptics have argued against the need for educating prisoners who are perceived as condemned, particularly education via the internet. This short conceptual article highlights the strengths and weaknesses of educating prisoners and draws forth the prospects and challenges therein and also assesses how e-learning may have influenced the prisoners to become either educated criminals or a reformed and changed personalities. This paper reports some study findings that were globally shared among academic and non-academic scholars concerning e-learning technologies and its integration in general education practices and prison education in particular through a survey of literature and personal observations. The key conclusion is that prison education has contributed more in reducing recidivism and lesser employability of released prisoners better than when formal education initiative was elusive in the prison service world over.